1982
DOI: 10.1002/ar.1092020402
|View full text |Cite
|
Sign up to set email alerts
|

Cell specialization in collecting tubules of the guinea pig kidney: Carbonic anhydrase activity and glycosaminoglycan production in different cells

Abstract: The distribution of complex carbohydrates has been investigated cytochemically at the light and electron microscope levels in collecting ducts of the guinea pig kidney. The dialyzed iron method demonstrated acidic complex carbohydrate ultrastructurally on the outer surface of the apical and the basolateral plasmalemma of the principal cells and in their maturing Golgi cisternae and secretory granules. Glycoconjugate in these sites stained for sulfate esters with the high iron diamine method but lacked reactivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1983
1983
2006
2006

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Moreover, LeHir et al (1982) have recently demonstrated with an ultrastructural, preembedment method, that binding of PNA in the collecting tubule of the rabbit kidney is restricted to the luminal surface of intercalated cells; whereas the principal cells are unstained. The cell types in collecting ducts of the guinea pig kidney have been further characterized by the localization of carbonic anhydrase exclusivelv in the intercalated cells (Sato and Spicer, 1982). The principal cells differed further in containing chondroitin sulfate-rich cytoplasmic granules and possessing a surface coat with chondroitin sulfate in contrast to the neutral glycoprotein comprising the intercalated cell's glycocalyx.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, LeHir et al (1982) have recently demonstrated with an ultrastructural, preembedment method, that binding of PNA in the collecting tubule of the rabbit kidney is restricted to the luminal surface of intercalated cells; whereas the principal cells are unstained. The cell types in collecting ducts of the guinea pig kidney have been further characterized by the localization of carbonic anhydrase exclusivelv in the intercalated cells (Sato and Spicer, 1982). The principal cells differed further in containing chondroitin sulfate-rich cytoplasmic granules and possessing a surface coat with chondroitin sulfate in contrast to the neutral glycoprotein comprising the intercalated cell's glycocalyx.…”
Section: Discussionmentioning
confidence: 99%
“…The antibodies against affinity purified CA I1 isoenzyme were raised in rabbits as described earlier in detail (15). The purity and specificity testing of these antibodies have been documented extensively (4,16). Rabbit anti-(Na+K)-ATPase antiserum used was a generous gift from Dr. G. Siegel (Department of Neurology, University of Michigan, Ann Arbor, MI) and was raised in rabbits against a mouse brain (Na+K)-ATPase catalytic unit as described earlier in detail (8).…”
Section: Methodsmentioning
confidence: 99%
“…The luminal surface of the distal nephron has a glycocalyx composed of glycosaminoglycans as well as other proteins that are set in a hydrated polysaccharide gel (43,44,61,65,96,97,109,126). Glycosaminoglycans consist of negatively charged disaccharide repeats that are linked to core proteins.…”
Section: Sensing Flow In Principal and Intercalated Cellsmentioning
confidence: 99%